Prolonged intracellular accumulation of light-inducible nanoparticles in leukemia cells allows their remote activation - Boto, Carlos (2017)
Leukaemia cells that are resistant to conventional therapies are thought to reside in protective niches. Here, we describe light-inducible polymeric retinoic acid (RA)-containing nanoparticles (NPs) with the capacity to accumulate in the cytoplasm of leukaemia cells for several days and release their RA payloads within a few minutes upon exposure to blue/UV light. Compared to NPs that are not activated by light exposure, these NPs more efficiently reduce the clonogenicity of bone marrow cancer cells from patients with acute myeloid leukaemia (AML) and induce the differentiation of RA-low sensitive leukaemia cells. Importantly, we show that leukaemia cells transfected with light-inducible NPs containing RA can engraft into bone marrow in vivo in the proximity of other leukaemic cells, differentiate upon exposure to blue light and release paracrine factors that modulate nearby cells. The NPs described here offer a promising strategy for controlling distant cell populations and remotely modulating leukaemic niches.